2018
DOI: 10.4103/sja.sja_239_17
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial comparing C Mac D Blade and Macintosh laryngoscope for nasotracheal intubation in patients undergoing surgeries for head and neck cancer

Abstract: Purpose:Several devices are available to take care of difficult airway, but C-MAC D-Blade has scant evidence of its use in nasotracheal intubation in a difficult airway scenario.Aims and Objectives:We compared the C-MAC D-Blade videolaryngoscope™, and the standard Macintosh laryngoscope for nasal intubation in patients with difficult airways selected by El-Ganzouri risk index using parameters of time and attempts required for intubation, glottic view in terms of Cormack–Lehane grade, ease of intubation, succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 17 publications
3
26
2
2
Order By: Relevance
“…Tseung et al [28]. reported that use of the GlideScope or Pentax AWS leads to reduced application of BURP, and Hazarika et al [29]. reported that use of the C-MAC D-Blade videolaryngoscope resulted in less need for additional maneuvers such as tube rotation, cuff inflation, and the use of Magill forceps than use of Macintosh direct laryngoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tseung et al [28]. reported that use of the GlideScope or Pentax AWS leads to reduced application of BURP, and Hazarika et al [29]. reported that use of the C-MAC D-Blade videolaryngoscope resulted in less need for additional maneuvers such as tube rotation, cuff inflation, and the use of Magill forceps than use of Macintosh direct laryngoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous trials have suggested that several intubating devices that provide non-line-of-sight views show a significantly improved conditions for NTI than conventional direct laryngoscopes. This is because these devices help to avoid deviation of the larynx from its original position and allow for easy placement of the ETT tip through the glottic inlet [29,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, the video laryngoscope (VDL) is a piece of medical equipment that supports intubating COVID-19 patients; its use is indicated in the guidelines for the treatment of such patients, as they provide a lower probability of contamination for medical staff who are in direct risk of contact with SARS-CoV-2 [4] It is well recognized that the use of VDLs has optimized the management of patients with difficult airways, and accordingly it has been included as part of the management of the airway guides of the American Society of Anesthesiologists (ASA) and the Difficult Airway Society (DAS) [5,6]. Furthermore, VDLs have had a great boom in developed countries, because they can help to better visualize the airways of patients who need to be intubated, since their use has shown great success in endotracheal intubation (EI) [7][8][9][10]. However, in developing countries, like ours, the approximate cost of VDL devices is between USD $2,000 and USD $22,000, while the cost of conventional laryngoscopes is within the range of USD $65 to USD $110.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review comparing VL versus DL for NTI showed that VL is particularly beneficial for patients with difficult airways [16]. However, only two randomized controlled trials (Airtriq and C-MAC versus Macintosh) were enrolled [7, 17]. It remains unclear whether non-channeled King Vision or McGrath MAC VL, compared with conventional laryngoscope, provide shorter intubation time and a higher first success rate for NTI when used by experienced provider in management of predicted difficult intubation.…”
Section: Introductionmentioning
confidence: 99%